HOUSING CHARACTER IN THE BORDER BEACH AREA OF CAMBAYYA - Idawarni Asmal; Nurmaida Amri (Journal of Architecture&ENVIRONMENT, 2018)
Cambayya is one of the areas in the Makassar city that has slum dwellings located on the water. The houses appears sporadically due to various community problems, such as the high price of land in the Makassar city and difficult to reach by the lower classes and the desire to live near the workplace. As a result, people are looking for low-cost dwellings, although not for rationing, poor sanitation conditions, and lacking facilities and infrastructure. The purpose of this research is to know the physical and non physical character of the residence located in the area starting directly adjacent to the water body up to  the Barukang road. The method used is the mix use method. In the housing study is divided into 3 zones, The first zone is in the dwelling above the water body, the 2nd zone in the dwelling above the coastal border and, the 3rd zone is in the dormitory adjacent to the main road of the area. The data is collected through the results of field observations in depth on the physical condition of the dwelling and the community. Medium data are measured through closed questionnaires submitted randomly to communities in each zone. The result obtained is the occupancy in each zone is different because of the influence of occupation, land ownership, and location of establishment.